Sport as a tool for separatist propaganda: theoretical approaches and practical countermeasures (case studies of the Republic of Azerbaijan and Ukraine) - Hajimuradov, Mais Saleh (Національний технічний університет "Харківський політехнічний інститут", 2026)
This paper examines the phenomenon of using sport as a means of promoting separatist sentiments and legitimizing territorial occupations. It analyzes the transformation of sport from a domain of leisure and fair competition into a political technology aimed at identity construction and the recognition of unrecognized entities. Special attention is given to the classification of sports organizations operating outside official international federations. Based on the policies of the Republic of Azerbaijan and Ukraine – both facing Russian-backed separatism and occupation – the study identifies key strategies for countering sports separatism and mechanisms for protecting national interests in the international sports environment.
Keywords: sport and politics; separatism; propaganda; Olympic Charter; sport; international sports environment